Supplementary Table S7 from In Vivo Screening Unveils Pervasive RNA-Binding Protein Dependencies in Leukemic Stem Cells and Identifies ELAVL1 as a Therapeutic Target - Ana Vujovic (15207479) (2025)
Table S7 shows (a) reproducible peaks and (b) GO analysis of ELAVL1-bound transcripts identified in the eCLIP-sequencing data set. The negatively enriched (c) and positively-enriched (d) gene sets identified by GSEA of ELAVL1-bound and differentially expressed transcripts from the RN2c RNA-sequencing data set are shown.